PELATIHAN PRODUKSI PANGAN HALAL SKALA INDUSTRI RUMAH TANGGA DALAM RANGKA PENINGKATAN KETAHANAN EKONOMI KELUARGA - Muh. Nashirudin; Luthfiana Zahriani; Joko Roby Prasetyo; Siti Rokhaniyah; Fardila Intan Rahmasari (LP2M Universitas Ibrahimy, 2023)
This activity provides training in household-scale halal food production to increase family economic resilience during the Covid-19 pandemic. Members of the KWT Ngudi Mulyo are ideal community partners in this activity. It has started a home-scale business by producing a variety of snacks and cakes, but is constrained by the marketing aspect, there is no halal certification and distribution permit. To provide solutions to these problems, we conduct community service activities based on community development. This community service activity not only provides training on halal products but also provides information related to halal certification, processing of distribution permits for food products, and marketing. Halal certification and distribution permits are important factors that increase the selling value of the product because they are quite a concern for consumers when buying food products. With the implementation of this training, it is hoped that it can strengthen the existence of the food product business that was started by KWT Ngudi Mulyo and its members. Businesses that exist and continue to grow will increase economic resilience.